Biological profiling of prospective antidepressant response in major depressive disorder: Associations with (neuro)inflammation, fatty acid metabolism, and amygdala-reactivity. (May 2017) - Mocking, R.J.T.; Nap, T.S.; Westerink, A.M.; Assies, J.; Vaz, F.M.; Koeter, M.W.J.; Ruhé, H.G.; Schene, A.H.
Highlights: Seventy unmedicated depressed patients had higher CRP and arachidonic acid than controls. Arachidonic acid was related with CRP and amygdala reactivity. In patients, these factors were longitudinally associated with antidepressant response. These findings corroborate a role for neuroinflammation in depression and treatment response. This may contribute to biomarker panel development to predict antidepressant success. Abstract: Background: A better understanding of factors underlying antidepressant non-response may improve the prediction of which patients will respond to what treatment. Major depressive disorder (MDD) is associated with alterations in fatty acid metabolism, (neuro)inflammation and amygdala-reactivity. However, their mutual relations, and the extent to which they are associated with prospective antidepressant-response, remain unknown. Purpose: To test (I) alterations in (neuro)inflammation and its associations with fatty acid metabolism and amygdala-reactivity in MDD-patients compared to controls, and (II) whether these alterations are associated with prospective paroxetine response. Methods: We compared 70 unmedicated MDD-patients with 51 matched healthy controls at baseline, regarding erythrocyte membrane omega-6 arachidonic acid (AA), inflammation [serum (high-sensitivity) C-reactive protein (CRP)], and in a subgroup amygdala-reactivity to emotional faces using functional magnetic resonance imaging (fMRI) (N = 42). Subsequently, we treated patients with 12 weeks paroxetine, and repeated baseline measures after 6 and 12 weeks to compare non-responders, early-responders (response at 6 weeks), and late-responders (response at 12 weeks). Results: Compared to controls, MDD-patients showed higher CRP ( p = 0.016) and AA ( p = 0.019) after adjustment for confounders at baseline. AA and CRP were mutually correlated ( p = 0.043). In addition, patients showed a more negative relation between AA and left amygdala-reactivity ( p = 0.014). Moreover, AA and CRP were associated with antidepressant-response: early responders showed lower AA ( p = 0.018) and higher CRP-concentrations ( p = 0.008) than non-responders throughout the study. Conclusion: Higher observed CRP and AA, their mutual association, and relation with amygdala-reactivity, are corroborative with a role for (neuro)inflammation in MDD. In addition, observed associations of these factors with prospective antidepressant-response suggest a potential role as biomarkers. Future studies in independent samples are needed to replicate and test the clinical applicability of these biological predictors for treatment response to result in a precision/personalized medicine approach for treatment.